Occlusion of the brachiocephalic trunk as a cause of recurrent chest pain in patient after previous coronary artery bypass grafting - Brykczyński, Mirosław; Ślozowski, Paweł; Grudniewicz, Seweryn (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Recurrent stenocardial pain after previous CABG is usually caused by the progress of the atherosclerosis. We are describing a case of a male, which underwent CABG procedure with the use of both thoracic arteries. This man came back after 10 years, presenting unusual symptoms during daily activities, that were suggesting recurrence of the coronary artery disease. Although, chest pain was connected with actions performed with the right hand. Extended diagnostics showed occlusion of the brachiocephalic trunk with coexisting critical stenosis of the left common carotid artery. Nevertheless, there was no neurological deficit present in this patient at the time of admission. After performing partial, superior resternotomy, bifurcated vascular prosthesis was implanted between ascending aorta and common carotid artery and subclavian artery on the right side. After 8 days of postoperative care patient was discharged, and went to undergo elective transcutaneus plastics of proximal narrowing of the left common carotid artery.